In search of the meaning of the work: overview of a qualitative study among executives - Coda, Roberto; Fonseca, Glaucia Falcone (Review of Business Management, 2007)
The present article is derived from of a study accomplished in a group of managers which objective aimed at understanding the meaning attributed by them to the work they perform. The research has been conducted according to a qualitative approach, based on Phenomenology. The collection of data was obtained through individual interviews, adopting as analytical process the method proposed by Giorgi (1985), involving four steps, and starting with verbal reports about living experiences to get to the understanding of the phenomenon. The results obtained indicated that, for each individual, work assumes a different meaning, a function related to his wishes and needs, transforming the work itself in an instrument for their self-actualization. The study also allowed the identification of 10 categories of meaning: 1) a means for taking part in something, belonging; 2) independence, autonomy; 3) an instrument for the transformation of society, of the organization; 4) a means for building something; 5) knowledge, enlargement; 6) a means for being useful; 7) a means for overcoming one’s limitations; 8) possibility of relating and establishing bonds with people; 9) a means for expressing knowledge and skills; 10) related to security, personal and family maintenance. These categories support the results obtained by the Meaning of Working – MOW – Research Group (1987) on the subject. It was also found out that if the individual attributes meaning to the work performed, there is a derived feeling of gratification and pleasure, which leads to the importance of studies about the Meaning of Work. From the results can benefit: 1) the professionals, since the investigations lead to questioning themselves and, therefore, to the search of a greater knowledge of their own wishes and needs, with a consequent quest for involvement in most meaningful activities; 2) the companies, which may provide an improved adjustment between organizational objectives and individual expectations, resulting in quality, synergy, and effectiveness. Key-words: Human behavior at work. Meaning of work. Psychological aspects in work situation. Intrinsic motivation.